Hit me : a Keller novel - Block, Lawrence (New York : Mulholland Books, 2013)
With a new wife and a baby on the way, Keller, a.k.a. Nicholas Edwards, is done killing people for money until a phone call from Dot draws him back into the old game, taking him to Dallas to settle a domestic dispute, to New York, where people might remember him.
Keywords: Keller, John (Fictitious character) -- Fiction; Assassins -- Fiction; Mystery fiction